2016
DOI: 10.1038/labinvest.2016.89
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of hepatic mast cells from cholestatic rats

Abstract: Mast cells (MCs) are immune cells that release histamine and other mediators. MC number increases after bile duct ligation (BDL) and blocking mast cell-derived histamine decrease biliary proliferation. We aimed to isolate and characterize MCs from cholestatic livers. Rats were subjected to BDL starting at 6 hrs and up to 14 days. MC infiltration was evaluated by toluidine blue. BDL rats were perfused using standard collagenase perfusion. Following enzymatic digestion, tissue was passed through a fine gauge nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“… 51 These studies are the first to demonstrate a synergistic interaction between MCs, cholangiocytes, and HSCs during cholestatic liver injury. 51 , 75 In addition, these studies indicate that MCs and MC-derived HA are key regulators of the biliary response in addition to the activation of HSCs during cholestatic-induced hepatic fibrosis.…”
Section: Mast Cellsmentioning
confidence: 96%
See 2 more Smart Citations
“… 51 These studies are the first to demonstrate a synergistic interaction between MCs, cholangiocytes, and HSCs during cholestatic liver injury. 51 , 75 In addition, these studies indicate that MCs and MC-derived HA are key regulators of the biliary response in addition to the activation of HSCs during cholestatic-induced hepatic fibrosis.…”
Section: Mast Cellsmentioning
confidence: 96%
“…The authors found that treatment with BDL saline-treated MC culture supernatants increased biliary proliferation and HSC activation, demonstrating a direct interaction between MCs, cholangiocytes, and HSCs. 75 More interestingly, when cultured cholangiocytes or HSCs were stimulated with culture supernatants of MCs collected from cromolyn sodium-treated BDL rats, biliary proliferation and HSC activation were reduced significantly. These studies support a strong relationship and regulation between MCs and HSCs during biliary damage and repair.…”
Section: Mast Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The infiltration (of myeloid lineage-derived cells from the bone marrow) and accumulation (differentiation of liver resident precursor cells, which can be differentiated in the presence of SCF) of MCs in the insulted liver has been shown in several studies and is unquestionable [101]. Even more, the isolation of MCs from liver of BDL-treated animals has been established [102]. It should be noted that not only the presence of MCs itself is of vital importance, but also the type of MCs within the liver (i.e., CTMCs or MMCs), when the functional interplay of cells is considered.…”
Section: Functional Interaction Of Mast Cells and Other Cell Typesmentioning
confidence: 99%
“…A study in human liver tissue demonstrated that the amount of tryptase/chymase-positive MCs is higher than tryptase-positive cells in healthy and chronically diseased livers [104]. The cells isolated from BDL rats were chymase- and tryptase-positive, reflecting that these cells most likely represent CTMCs [102].…”
Section: Functional Interaction Of Mast Cells and Other Cell Typesmentioning
confidence: 99%